The evaluation of a new lower-body reaction time test - Spiteri, T.; Cochrane, J. L.; Nimphius, S. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to investigate the reliability of 2 lower-body reaction time (RT) tests to determine the differences in RTs between genders and compatible and incompatible conditions. Fifteen male and female (N = 30; 22.63 ± 2.88 years; 175.31 ± 8.72 cm; 67.33 ± 9.71 kg) sport science students participated in this study. Subjects were required to complete 2 lower-body RT tests responding to an arrow during compatible (same direction) and incompatible (opposite direction) stimulus-response conditions. The "simple" foot RT test required subjects to step quickly on the appropriate mat, as directed by the stimulus, with response time being measured. The "complex" foot RT test required subjects to leap off a force plate to the appropriate mat in response to the stimulus, with RT, movement time (MT), and total movement time (TMT) being measured. Intraclass correlation coefficient, coefficient of variation, and paired samples t-test (p < 0.05) were calculated for all variables. High reliability was observed for both tests between compatible and incompatible conditions. Significant differences (p < 0.05) were observed between genders for RT during the simple RT test. Significant differences (p < 0.05) were observed for MT and TMT during compatible and incompatible conditions for the complex RT test. In conclusion, both tests are reliable to determine lower-body RTs during both conditions. Movement time and TMT during the complex RT test were significantly different, suggesting that MT could be the discriminating factor between conditions and also genders. Examining lower-body RTs during a movement commonly observed in sports may provide coaches more details about the athletes' cognitive and athletic ability, enabling the components of RT to be trained.